The Implementation of the STAD Cooperative Learning Model Assisted by Audiovisual Media in Pancasila Education to Improve Learning Motivation and Learning Outcomes of Grade VII B Students at SMP Negeri 3 Susut - Diah Puspitasari, Anak Agung; Sanjaya, Dewa Bagus; Sidariyanti, Ni Nyoman Asri (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
This study aims to improve students’ learning motivation and learning outcomes through the implementation of the STAD (Student Team Achievement Division) cooperative learning model assisted by audiovisual media in Pancasila Education. The research was conducted on Grade VII B students at SMP Negeri 3 Susut. This study was motivated by the low level of students’ learning motivation and learning outcomes, which were influenced by teacher-centered learning methods and limited use of engaging learning media. The research method used was Classroom Action Research (CAR), conducted in several cycles consisting of planning, action, observation, and reflection. Data were collected through observation, learning achievement tests, and learning motivation questionnaires. The results indicate that the implementation of the STAD cooperative learning model assisted by audiovisual media significantly improves students’ learning motivation and has a positive impact on their learning outcomes in Pancasila Education. Therefore, the STAD learning model assisted by audiovisual media is effective as an alternative instructional approach to enhance the quality of the learning process and student achievement. Keywords: STAD cooperative learning model, audiovisual media, learning motivation, learning outcomes, Pancasila Education.